2007
DOI: 10.1583/06-1906.1
|View full text |Cite
|
Sign up to set email alerts
|

Direct Videoscopic Approach to the Descending Thoracic Aorta for Aortic Arch Endograft Delivery: Evaluation in a Porcine Model

Abstract: A direct videoscopic approach to the descending thoracic aorta proved a feasible technique for endograft delivery to the aortic arch in a porcine model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Of the 46 selected studies, 30, 15, and 1 reported swine, ovine, and bovine data, respectively. 2 , 10 53 In the 1 paper we found describing bovine arterial dimensions, only thoracic aorta measurements were determined to be relevant in this study. We found no study describing aortic arch branch diameters in calves and only 1 study in sheep reporting brachiocephalic trunk diameters.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 46 selected studies, 30, 15, and 1 reported swine, ovine, and bovine data, respectively. 2 , 10 53 In the 1 paper we found describing bovine arterial dimensions, only thoracic aorta measurements were determined to be relevant in this study. We found no study describing aortic arch branch diameters in calves and only 1 study in sheep reporting brachiocephalic trunk diameters.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our group developed a videoscopic approach for direct puncture of the descending thoracic aorta for endograft delivery to the aortic arch. 3 Tested in a porcine model, the descending thoracic aorta proved easily accessible after deflation of the left lung, without the need for dissection or retraction. The use of a double-felted purse-string suture provided adequate hemostasis after catheter removal without the need for aortic cross clamping, while blood loss was kept to a minimum (mean 143 mL).…”
Section: Discussionmentioning
confidence: 99%
“…We recently described a direct videoscopic approach to the descending thoracic aorta for endograft delivery to the aortic arch in a porcine model. 3 Due to improved maneuverability and fewer restrictions on introducer sheath size, the See commentary page 19 direct videoscopic approach may facilitate branch vessel cannulation and branch graft delivery, especially in those cases where branch vessels arise from the aorta in a difficult angle. The purpose of this study was to assess the feasibility of a direct videoscopic approach to the descending thoracic aorta for branched endograft delivery to the aortic arch and the pararenal aorta in a human cadaver circulation model.…”
mentioning
confidence: 99%